2022
DOI: 10.1021/acs.jpclett.2c00194
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafast Excitation Energy Transfer Dynamics in the LHCII–CP29–CP24 Subdomain of Plant Photosystem II

Abstract: We measure the two-dimensional electronic spectra of the LHCII(M)− CP29−CP24 complex in photosystem II (PSII) and provide the first study of the ultrafast excitation energy transfer (EET) processes of an asymmetric and native lightharvesting assembly of the antenna of PSII. With comparisons to LHCII, we observe faster energy equilibrations in the intermediate levels of the LHCII(M)−CP29−CP24 complex at 662 and 670 nm. Notably, the putative "bottleneck" states in LHCII exhibit faster effective dynamics in the L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 56 publications
0
23
0
Order By: Relevance
“…The timescale of the observed dynamics described above in the C 1 S 1 complex can be further analyzed using lifetime density analysis (LDA) on the 2D spectroscopic data. We use the LDA procedure with Tikhonov regularization described in ( 58 ) and our previous work ( 25 ). Figure 4A shows an integrated lifetime density map (LDM) of the C 1 S 1 2D spectra with the excited region at λ τ = 640 to 660 nm.…”
Section: Resultsmentioning
confidence: 99%
“…The timescale of the observed dynamics described above in the C 1 S 1 complex can be further analyzed using lifetime density analysis (LDA) on the 2D spectroscopic data. We use the LDA procedure with Tikhonov regularization described in ( 58 ) and our previous work ( 25 ). Figure 4A shows an integrated lifetime density map (LDM) of the C 1 S 1 2D spectra with the excited region at λ τ = 640 to 660 nm.…”
Section: Resultsmentioning
confidence: 99%
“…The maximal emission of the rods is at 645 nm, and the entire phycobilisome complex emits at ∼665 nm. These features cannot be deconvolved at room temperature because of the broad lineshapes, as seen with other large photosynthetic proteins. , Low-temperature studies of the phycobilisome are challenging because of the propensity of the complex to disassemble, and only a few fluorescence studies have been reported. Similar diagonal elongation in 2D spectra is also observed in other light-harvesting antennae like PSI and LHCII-CP29-CP24 . The negative feature seen below the diagonal at detection wavelengths (λ det ) between 660 and 680 nm has previously been attributed to an electrochromic shift of the excited states of neighboring chromophores, which induces a PIA feature .…”
Section: Resultsmentioning
confidence: 93%
“…Excitonic coupling and energy transfers are the typical processes that can be directly observed in 2DES, as has been applied to several previous studies on various complex systems. ,, In addition, one phenomenon that can be measured in 2DES but is inaccessible using conventional TA spectroscopy is ultrafast spectral diffusion, which dictates the evolution of the 2D peakshapes due to the ability of 2DES to correlate the excitation and detection frequencies . In ultrafast spectral diffusion, the excited system fluctuates and evolves to different frequencies in the time scale of femtoseconds to picoseconds due to interactions of the system with the environment, including coupling to vibrations of the proteins and/or solvent molecules in the environment as well as lattice phonon modes. These ultrafast spectral diffusions take place at a much shorter time scale of the spectral diffusion measured by single-molecule PL studies on nanocrystals, which are at time scales of milliseconds to seconds. One measure of the ultrafast spectral diffusion dynamics of an ensemble is the frequency-fluctuation correlation function (FFCF). ,, FFCF is a useful quantity as it connects microscopic molecular and atomic level dynamics directly to the nonlinear optical spectroscopic measurements such as 2DES.…”
mentioning
confidence: 99%